Design of wire bond inductors and high-speed printed circuit board - Mohamed Mansoor Mohamed Mafraz (2017)
Wire bond technology is a matured and dominant interconnect methodology compared to other chip interconnect methodologies. The parasitic components of the bond wire, especially in high speed operating conditions, have to be modeled accurately before utilizing the bond wire in such designs. Our research group is working on a novel high-efficiency Class-E switched-mode Power Amplifier (PA) IC for digital RF transmitters [5]. The PA employs a novel digitally-controlled matching network that utilizes switched-capacitors and wire bonds to the board. This requires accurate modeling of the required wire bonds for its inductance. Our research group also works on a novel high-rate Analog-to-Digital Converter (ADC) for switched-mode DC-DC converters [4]. Both of these designs operate in high speed conditions. This Master of Science dissertation project pertains to the work of modeling, designing, and realizing high quality factor (Q) wire bond inductors for the Radio Frequency power amplifier (RF PA) IC, and thereafter designing high-speed Printed circuit boards (PCBs) for measuring the performance of the RFPA and ADC ICs. The wire bond inductors are modeled using the ADS modeling and simulation tool in the required frequency range of 2-3GHz. The simulation results are verified using PCB implementation. The measurement results are presented and utilized for the design of high-speed RFPA IC test board. The high-speed PCBs are carefully to mitigate any spurious behaviors.